1996
DOI: 10.1007/bf00017799
|View full text |Cite
|
Sign up to set email alerts
|

The conserved ELK-homeodomain of KNOTTED-1 contains two regions that signal nuclear localization

Abstract: Nuclear localization serves as a regulatory mechanism in the activity of several transcription factors. KNOTTED-1 (Kn1) is a homeodomain protein likely to regulate vegetative development in maize. At least twelve genes related to Kn1 are known in maize and six in Arabidopsis. Ectopic expression of the maize, rice and Arabidopsis Kn1-related genes have been shown to alter cell fate determination. In this paper, we study the nuclear localization capabilities of the Kn1 homeodomain and the proximal amino acid res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 57 publications
0
32
0
Order By: Relevance
“…The second protocol is based upon a phenol:chloroform extraction and LiCl precipitation protocol as describe by Das et al (1990). These protocols have been used to isolate RNA from leaf tissue in model plants such as arabidopsis, tobacco and maize (Das et al, 1990;Meisel and Lam, 1996;Silva et al, 1999). However, use of such protocols on peach fruits yielded poor quality RNA with high levels of polysaccharides, polyphenolic compounds, and protein contaminants as determined by A240/260 and A260/280, respectively (Logemann et al, 1987;Manning 1990) (Table I).…”
Section: Resultsmentioning
confidence: 99%
“…The second protocol is based upon a phenol:chloroform extraction and LiCl precipitation protocol as describe by Das et al (1990). These protocols have been used to isolate RNA from leaf tissue in model plants such as arabidopsis, tobacco and maize (Das et al, 1990;Meisel and Lam, 1996;Silva et al, 1999). However, use of such protocols on peach fruits yielded poor quality RNA with high levels of polysaccharides, polyphenolic compounds, and protein contaminants as determined by A240/260 and A260/280, respectively (Logemann et al, 1987;Manning 1990) (Table I).…”
Section: Resultsmentioning
confidence: 99%
“…To facilitate identification of the functional NLS or NLSs, we used a transient assay involving the biolistic bombardment of various NPR1-GFP fusion constructs into onion epidermal cells. This assay is a quick and effective means of identifying the NLSs in a variety of plant proteins (Varagona et al, 1992;Meisel and Lam, 1996; van den Ackerveken et al, 1996). On the basis of the constitutive expression of the BGL2::GUS reporter gene detected in this assay, the onion cells appear to represent the SARinduced state (data not shown).…”
Section: Nuclear Targeting Of Npr1 Requires a Bipartite Nuclear Localmentioning
confidence: 99%
“…The HD is required for DNA binding (Smith et al, 2002;Viola and Gonzalez, 2009) and intercellular trafficking (Lucas et al, 1995;Kim et al, 2005;Winter et al, 2007b;Bolduc and Hake, 2009). However, the role of the ELK domain is less understood, although it is considered to be required for protein-protein interaction (Vollbrecht et al, 1991;Kerstetter et al, 1994) and for nuclear localization signal (NLS) sequences (Meisel and Lam, 1996). Cole et al (2006) indicated that STM does not contain an NLS, and in the rice KNOX1 gene OSH15, the ELK domain is not required for nuclear localization, DNA binding, or homodimer formation, although it was shown to have a role in suppressing transactivation activity (Nagasaki et al, 2001).…”
mentioning
confidence: 99%